1983
DOI: 10.1161/01.res.52.6.697
|View full text |Cite
|
Sign up to set email alerts
|

Relation between intracellular sodium and twitch tension in sheep cardiac Purkinje strands exposed to cardiac glycosides.

Abstract: Changes in intracellular sodium ion activity (aiNa) produced by several cardiac glycosides were correlated with twitch tension in sheep cardiac Purkinje strands. Simultaneous measurements of aiNa and twitch tension were obtained through the use of Na-sensitive intracellular microelectrodes (ETH 227) in Purkinje preparations stimulated at a frequency of 1 Hz. All concentrations of ouabain, acetylstrophanthidin, and actodigin that were tested caused an increase in aiNa immediately before, or coincident with, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3

Year Published

1984
1984
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 22 publications
5
37
3
Order By: Relevance
“…In sheep Purkinje fibres, Boyett et al (1986) observed hysteresis in the relation between twitch tension and aNa (measured with Na+-sensitive microelectrodes) on application and wash-off of strophanthidin; with 10-5 M-strophanthidin the maximum width of the hysteresis loop was I + 0-1 mm aNa (Levi & Boyett, 1991). The hysteresis had not been reported by previous authors working with sheep Purkinje fibres (Lee & Dagostino, 1982;Wasserstrom et al 1983) and has been discounted as an artifact associated with the Na+-sensitive microelectrode (Lee, 1985). In the present study we have observed a similar hysteresis in the relation between the twitch and aia in guinea-pig ventricular myocytes on application and wash-off of strophanthidin (Fig.…”
Section: Discussion Ana In Ventricular Myocytessupporting
confidence: 83%
See 1 more Smart Citation
“…In sheep Purkinje fibres, Boyett et al (1986) observed hysteresis in the relation between twitch tension and aNa (measured with Na+-sensitive microelectrodes) on application and wash-off of strophanthidin; with 10-5 M-strophanthidin the maximum width of the hysteresis loop was I + 0-1 mm aNa (Levi & Boyett, 1991). The hysteresis had not been reported by previous authors working with sheep Purkinje fibres (Lee & Dagostino, 1982;Wasserstrom et al 1983) and has been discounted as an artifact associated with the Na+-sensitive microelectrode (Lee, 1985). In the present study we have observed a similar hysteresis in the relation between the twitch and aia in guinea-pig ventricular myocytes on application and wash-off of strophanthidin (Fig.…”
Section: Discussion Ana In Ventricular Myocytessupporting
confidence: 83%
“…Another factor contributing to the difference between ventricular myocytes and Purkinje fibres may be that there is greater scope for an increase in the strength of contraction in Purkinje fibres than in ventricular muscle. For example, the work of Eisner et al (1981Eisner et al ( , 1984 and Wasserstrom et al (1983) shows that in Purkinje fibres twitch tension can increase by up to 10 times during Na+-K+ pump inhibition. In contrast, in cat ventricular muscle (rate of stimulation, 0 67 Hz; 30°C; 1t12 mM-bathing Ca2+) an increase in the bathing Ca2+concentration to maximise twitch tension only increased twitch tension by 2 2 times (Allen, 1975).…”
Section: Intracellular Sodium Anvd Contractionmentioning
confidence: 99%
“…Ouabain has been thought to increase the contraction through a Na+-Ca2+ exchange mechanism (Reuter & Seitz, 1968;Sheu & Fozzard, 1982;Wasserstrom et al, 1983;Eisner et al, 1984;Vassalle & Lee, 1984;Wier & Hess, 1984;Grupp et al, 1985). Ouabain inhibits Na'-K' ATPase and results in an accumulation of [NaJ]i.…”
Section: Discussionmentioning
confidence: 99%
“…This effect correlates with an increase in intracellular Ca2+ Allen et al, 1984) and the development of a ' Author for correspondence. positive inotropic effect (Lee et al, 1980;Wasserstrom et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with ion-selective microelectrodes have provided convincing evidence that cardiac glycosides increase intracellular Na' activity in mammalian myocardium, probably by inhibition of active Na' extrusion from the cell via the ATP-driven Na' pump (Ellis, 1977;Deitmer & Ellis, 1978; Lee et al, 1980;Cohen et al, 1982;Daut, 1982;Wasserstrom et al, 1983). This effect correlates with an increase in intracellular Ca2+ Allen et al, 1984) and the development of a ' Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%